THE MACROECONOMIC DETERMINANTS OF POLITICAL STABILITY IN POST-SOVIET COUNTRIES MOVED FROM CENTRALLY PLANNED ECONOMY TO FREE MARKET ECONOMY - İzzet Taşar (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
Thesuccessful integration of the post-Soviet countries to European Union and toother market economies via economic and political transition has been asubstantial issue for international economic and political relations. Amid allthe structural changes it has been of significant importance for the policy makersto set forth the macroeconomic determinants of the political stability intransition economies moved from centrally planned economy through marketeconomy. In this study the macroeconomic determinants of the politicalstability within the transition economies between 2002-2015 have beeninvestigated by utilizing the panel data method. Depending on the empiricalanalysis, it has been concluded that GDP per capita and consumer price indexare the most important macroeconomic factors affecting the political stabilityin the short-term.